A Post-Pandemic Architecture: Mandalika Bus Terminal Design with Locality Approaches - Kusumaningthiyas, Wike Adisti; Gazalba, Zaedar; Bachtiar, Jasmine Chanifah Uzdah (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
The spread of the COVID-19 virus since it first appeared in Wuhan (2019) to all regions of the world has had implications in various sectors and endangered people's lives. As a result, the entire world is under lockdown and travel is prohibited. Public transport as community commuting could increase the risk of virus transmission widely. Therefore, some new design ideas are approached to facilitate people mobility and to mitigate and hinder the spread of virus. This study aims to address the ongoing public health problem posed by the COVID-19 outbreak by designing a post-pandemic bus terminal in Mataram City, Indonesia, incorporating health protocols and physical distancing to prevent COVID cases. The study used architecture design methods by collecting some data onsite and offsite, analysing the data through site analysis and programming, and then proposing design concepts for the bus terminal. The results show a bus terminal building design that incorporates green elements, flexible furniture, signage to promote physical distancing and minimize the spread of COVID-19 and incorporates Sasak Architecture concepts, creating a distinctive, and visually appealing appearance. This study concludes that the design of a bus terminal building can play a crucial role in promoting physical distancing and minimizing the spread of COVID-19.